PENGEMBANGAN PAKET WISATA DI DESA TODO SATAR MESE UTARA, MANGGARAI, NUSA TENGGARA TIMUR - Skolastika Syukur, Mardiana; Sasrawan Mananda, IGPB.; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024), 2024)
East Nusa Tenggara Province is one of the provinces in Indonesia which is located in the Eastern region of Indonesia and has various tourism potentials, namely cultural tourism potential, natural tourism potential and artificial tourism potential. Todo Village is a tourist attraction located in Manggarai district which has its own history and culture. Todo Village has very interesting tourism potential to be developed in a tour packageData collection techniques in this study are observation, interviews, literature studies and documentation. The informant determination technique in this study is purposive sampling. The analysis technique used is qualitative descriptive. The aim of this research is to describe the development of tourism packages in Todo Village, North Satar Mese District, Manggarai Regency. The data collection techniques used in this research are observation, interviews and documentation. The research method carried out in this research is qualitative data analysis using purposive sampling. The data sources used in this research are primary data and secondary data. Determining the informants in this research are key informants and base informants.The results of this research show that in Todo Village there are eleven tourism potentials consisting of natural tourist attractions and cultural tourist attractions packaged in a tour package. These potentials are packaged into 2 tour packages, namely, Todo Culture Tour and Todo Traditional Village with 1 day tour and 2 day 1 night tour activities.